2017
DOI: 10.1002/1873-3468.12624
|View full text |Cite
|
Sign up to set email alerts
|

Smurf1 controls S phase progression and tumorigenesis through Wee1 degradation

Abstract: Smad ubiquitination regulatory factor 1 (Smurf1) is a HECT-type E3 ubiquitin ligase that regulates several important signaling pathways, including the bone morphogenetic protein pathway and the transforming growth factor-beta (TGF-β) signaling pathway. However, the function of Smurf1 in cell cycle progression remains unclear. Here, we demonstrate that silencing of Smurf1 results in S phase arrest, confirming that Smurf1 is required for S phase progression. Furthermore, we demonstrate that Smurf1-mediated S pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Smurf1, as a E3 Ubiquitin Ligases, could degrade the key protein in the TGF-β1 induced pathway. 27,28 PTEN, an upstream molecule of PI3K-Akt-mTOR pathway, could dephosphorylate the PI3K to down-regulate the activation of PI3K-Akt-mTOR pathway. 29,30 WWP2, another E3 Ubiquitin Ligases, could degrade PTEN by ubiquitination pathway to suppress tumourigenesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Smurf1, as a E3 Ubiquitin Ligases, could degrade the key protein in the TGF-β1 induced pathway. 27,28 PTEN, an upstream molecule of PI3K-Akt-mTOR pathway, could dephosphorylate the PI3K to down-regulate the activation of PI3K-Akt-mTOR pathway. 29,30 WWP2, another E3 Ubiquitin Ligases, could degrade PTEN by ubiquitination pathway to suppress tumourigenesis.…”
Section: Discussionmentioning
confidence: 99%
“…The potential mechanisms of Bortezomib inhibiting the expression of Smurf1 maybe that Bortezomib promotes the expression of inhibitory miRNA, such as miR-424(322). Smurf1, as a E3 Ubiquitin Ligases, could degrade the key protein in the TGF-β1 induced pathway 27,28. PTEN, an upstream molecule of PI3K-Akt-mTOR pathway, could dephosphorylate the PI3K to down-regulate the activation of PI3K-Akt-mTOR pathway 29,30.…”
mentioning
confidence: 99%
“…Christopher C. Porter et al reported that the inhibition of WEE1 prevents cytarabine-induced S phase arrest in acute myeloid leukemia 14. Moreover, Wei et al demonstrated that WEE1 degradation contributes to Smurf1-regulated S phase progression 15. Therefore, WEE1 upregulation may explain the S phase arrest after SMYD3 inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…During M-phase, ubiquitin-dependent protein degradation is responsible for the downfall of WEE1. Initially, during the G2-M transition, PLK1, CDK1, and CK2 phosphorylation at S53, S123, and S121 residues generate phosphodegrons (PDs), and CDC34 ubiquitination of WEE1 allows SCF (skp1/cul1/F-box) β-TrCP (β-transduction repeat-containing protein), Tome-1 (trigger-of-mitotic-entry 1), Smurf1 (Smad ubiquitination regulatory factor1), and Pof1/3 (Promoter of Filamentation1/3) (in fission yeast) mediated WEE1 degradation. However, in a later study, WEE1 was found to interact with the β-subunit of CK2, but this interaction showed no remarkable influence on WEE1 kinase activity . Another mechanism reported is the nuclear export of WEE1.…”
Section: Introductionmentioning
confidence: 99%